Childhood epilepsy in the Department of child health Dr. Pirngadi Hospital Medan - Bistok Saing; Helmi Lubis; Leonard Napitupulu; Helena Siregar (Indonesian Pediatric Society, 1984)
A retrospective study of epilepsy cases had been done from January 1978 to December 1982. The aims of this study was to know the incidence, type and result of treatment of epilepsy in the Department of Child Health Dr. Pirngadi Hospital, Medan, Indonesia. 103 cases of epilepsy were investigated. This was 0,10% of total patients in OPD as well as inpatients during this period, consisting of 56,32% boys and 43,68% girls. According to the classification of the Intemational League Against Epilepsy (ILAE) all of the patients had generalized epilepsy, consisting of 68,93% primary generalized epilepsy and 31.07% secondary generalized epilepsy. Thus the incidence of epilepsy was low, with a preponderance of primary generalized epilepsy. Of these patients only 18.44% came regularly for control. They were treated with a single drug namely phenobarbital, with good results.